Comparative neurobehavioral and histopathological toxicity induced by chronic exposure to metallic oxide nanoparticles and perovskite nanomembrane - Jararr, Bashir; Almansour, Mansour; Al-Doaiss, Amin; Jarrar, Qais; Zainudin, Edi Syams; Lee, Su Jun; Sewelam, Amal (Springer Science and Business Media Deutschland GmbH, 2025)
Background: Nanoparticles (NPs) are increasingly used in medicine, industry, agriculture, cosmetics, drug delivery, and energy storage. Despite their widespread use, their potential toxicity, particularly their effects on behavior, remains poorly understood. This study aimed to investigate behavioral and neuronal changes following chronic exposure to four types of NPs: silicon dioxide, nickel oxide, cobalt oxide, and perovskite nanomembrane. Methods: Eighty adult male BALB/c mice were divided into four treatment groups and four control groups. Treated mice received daily intraperitoneal injections of silicon dioxide, nickel oxide, cobalt oxide, or perovskite for 35 days, while controls received the corresponding vehicle. All mice underwent eight neurobehavioral tests. Brain tissues were collected for histological and immunohistochemical analysis. Results: NPs-exposed mice exhibited anxiety- and depression-like behaviors, increased stress, thigmotaxis, reduced locomotion, and impaired exploratory activity. Spatial learning and both reference and working memory were also compromised. Histological analysis revealed neuronal shrinkage and pyknosis in the prefrontal cortex, hippocampus, and cerebellum, along with gliosis, vascular changes, perivascular edema, neuronophagia, and spongiosis. Moreover, a positive inducible nitric oxide synthase (iNOS) immunoreactivity has been increased by the exposure to different types of NPs indicating nitrosative stress with subsequent oxidative stress. Conclusions: Chronic exposure to NPs induces nitrosative and subsequent oxidative stresses-related neuronal damage and behavioral alterations, potentially disrupting brain function. Among the tested NPs, perovskite nanomembranes displayed the most severe effects, followed by Co3O4, NiO, and SiO2 NPs. Further studies are needed to elucidate the relationship between behavioral outcomes and neuronal pathology caused by long-term NP exposure.